Development, implementation and evaluation of a diet and physical activity intervention targeting rural Australian adults with or at risk of metabolic syndrome - Blackford, Krysten Deanne (Curtin University, 2016)
Metabolic syndrome significantly increases the risk of developing type 2 diabetes mellitus and cardiovascular disease, particularly for older adults in rural areas of Australia. This study aimed to determine the most effective intervention strategies for the high risk target group, and the effect on health outcomes. The findings highlight the importance of health promotion to empower individuals to adopt and maintain healthy dietary and physical activity behaviours before the development of chronic disease.